2019
DOI: 10.1177/1465312519838555
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eruptive coronal resorption of unerupted molar teeth in orthodontic patients

Abstract: Pre-eruptive coronal resorption (PCR) is a rare phenomenon affecting unerupted permanent teeth. The aetiology of PCR is unknown and is often detected as an incidental finding. The prognosis of affected teeth can be extremely variable and may involve multidisciplinary management. The lower second permanent molars are commonly affected. The following is a description of three clinical cases of PCR affecting lower permanent molars in orthodontic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Based on previous studies, there appears to be no correlation between PEIR and systemic factors, such as race, gender, or fluoride supplementation. 23 25 , 43 However, Al-Tuwirqi and Seow found that this condition was associated with the ectopic position of the affected tooth or with delayed dental development of at least 6 months 5 , 23 , 32 , 43 Özden and Acikgoz also stated a correlation with supernumerary teeth. 11 , 40 In addition, Uzun et al reported two clinical cases presenting simultaneously herpes zoster virus and PEIR defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, there appears to be no correlation between PEIR and systemic factors, such as race, gender, or fluoride supplementation. 23 25 , 43 However, Al-Tuwirqi and Seow found that this condition was associated with the ectopic position of the affected tooth or with delayed dental development of at least 6 months 5 , 23 , 32 , 43 Özden and Acikgoz also stated a correlation with supernumerary teeth. 11 , 40 In addition, Uzun et al reported two clinical cases presenting simultaneously herpes zoster virus and PEIR defects.…”
Section: Discussionmentioning
confidence: 99%
“…No association has been reported between PEIR and race, gender, medical conditions, systemic diseases, systemic factors, or the use of fluoride supplementation. 23 25 However, a significant correlation was found between the ectopic position of teeth and PEIR. 11 , 23 …”
Section: B Ackgroundmentioning
confidence: 94%